Avoiding bicycle collisions: Experience on safety bike behavior among Italian bicycle users, individual and conspicuity characteristics. Issue 5 (27th May 2020) - Ferraro, Ottavia E.; Orsi, Chiara; Popa, Ioana; Montomoli, Cristina; Morandi, Anna
Abstract: Biking is a means of sustainable transport and is expected to grow over the next few years. Cyclists are more vulnerable road users than car, bus, and truck drivers. This is a pilot study aimed at generating information on the use of bike safety equipment and high-visibility clothing among Italian adult cyclists and identifying factors associated with safety gear use. Data from a European study involving a web survey of 2, 470 cyclists were analyzed. The sample was composed of 62% males, the sample median age was 54, and the proportion of those using a city bike was about 72%. The association between individual and bike characteristics and the use of bicycle safety equipment—light and reflectors—and high-visibility clothing were studied with regression logistic models. The results showed that cyclists who use conspicuous clothing were males, older, came from the South, rode more than 60 km, and used bike safety devices. Riders who used all or at least one item of safety gear rode city bikes and used high-visibility clothing. The data provided a first step in filling the gap in knowledge concerning individual-based safety measures and bike safety equipment use in Italy.